Improved Posterolateral Lumbar Spinal Fusion Using a Biomimetic, Nanocomposite Scaffold Augmented by Autologous Platelet-Rich Plasma - Van Eps, Jeffrey L.; Fernandez-Moure, Joseph S.; Cabrera, Fernando J.; Taraballi, Francesca; Paradiso, Francesca; Minardi, Silvia; Wang, Xin; Aghdasi, Bayan; Tasciotti, Ennio; Weiner, Bradley K. (Frontiers in Bioengineering and Biotechnology, 2021)
Remodeling of the human bony skeleton is constantly occurring with up to 10% annual bone volume turnover from osteoclastic and osteoblastic activity. A shift toward resorption can result in osteoporosis and pathologic fractures, while a shift toward deposition is required after traumatic or surgical injury. Spinal fusion represents one such state, requiring a substantial regenerative response to immobilize adjacent vertebrae through bony union. Autologous bone grafts were used extensively prior to the advent of advanced therapeutics incorporating exogenous growth factors and biomaterials. Besides cost constraints, these applications have demonstrated patient safety concerns. This study evaluated the regenerative ability of a nanostructured, magnesium-doped, hydroxyapatite/type I collagen scaffold (MHA/Coll) augmented by autologous platelet-rich plasma (PRP) in an orthotopic model of posterolateral lumbar spinal fusion. After bilateral decortication, rabbits received either the scaffold alone (Group 1) or scaffold with PRP (Group 2) to the anatomic right side. Bone regeneration and fusion success compared to internal control were assessed by DynaCT with 3-D reconstruction at 2, 4, and 6 weeks postoperatively followed by comparative osteogenic gene expression and representative histopathology. Both groups formed significantly more new bone volume than control, and Group 2 subjects produced significantly more trabecular and cortical bone than Group 1 subjects. Successful fusion was seen in one Group 1 animal (12.5%) and 6/8 Group 2 animals (75%). This enhanced effect by autologous PRP treatment appears to occur via astounding upregulation of key osteogenic genes. Both groups demonstrated significant gene upregulation compared to vertebral bone controls for all genes. Group 1 averaged 2.21-fold upregulation of RUNX2 gene, 3.20-fold upregulation of SPARC gene, and 3.67-fold upregulation of SPP1 gene. Depending on anatomical subgroup (cranial, mid, caudal scaffold portions), Group 2 had significantly higher average expression of all genes than both control and Group 1 - RUNX2 (8.23-19.74 fold), SPARC (18.67-55.44 fold), and SPP1 (46.09-90.65 fold). Our data collectively demonstrate the osteoinductive nature of a nanostructured MHA/Coll scaffold, a beneficial effect of augmentation with autologous PRP, and an ability to achieve clinical fusion when applied together in an orthotopic model. This has implications both for future study and biomedical innovation of bone-forming therapeutics.